STUDY AND DETERMINATION OF THE SENSITIVITY OF MICROORGANISMS TO CHEMOTHERAPEUTIC DRUGS AND ANTIBIOTICS (International journal of artificial intelligence, 2026)
This article provides a scientific analysis of the mechanisms of action of chemotherapeutic agents and antibiotics on microbial activity, as well as the methods used to determine their sensitivity. The excessive or improper use of antibiotics has led to an increase in resistant forms of microorganisms. Therefore, assessing microbial sensitivity to antibiotics is of great clinical importance for the correct treatment of infections, the rational selection of drugs, and the prevention of drug-resistant strains. The article discusses both theoretical and practical aspects of methods such as disk diffusion, minimum inhibitory concentration (MIC), and the automated VITEK system.